2017
DOI: 10.1210/jc.2017-02140
|View full text |Cite
|
Sign up to set email alerts
|

Transfer and Metabolism of Cortisol by the Isolated Perfused Human Placenta

Abstract: Context:Fetal overexposure to glucocorticoids in utero is associated with fetal growth restriction and is postulated to be a key mechanism linking suboptimal fetal growth with cardiovascular disease in later life.Objective:To develop a model to predict maternal-fetal glucocorticoid transfer. We hypothesized placental 11-β-hydroxysteroid dehydrogenase-type 2 (11β-HSD2) would be the major rate-limiting step in maternal cortisol transfer to the fetus.Design:We used a deuterated cortisol tracer in the ex vivo plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 42 publications
3
54
0
Order By: Relevance
“…It is now widely accepted that 11β‐hydroxysteroid dehydrogenase 2 (11β‐HSD2), a glucocorticoid‐inactivating enzyme, acts as the placental glucocorticoid barrier 4,5 . Several studies have indicated that 11β‐HSD2 catalyzes active glucocorticoids, such as cortisol, into their inactive products, such as cortisone, thus preventing glucocorticoids from passing maternal circulation into the fetus 6‐8 . Ontogeny studies indicate that the expression of 11β‐HSD2 is initiated at a very early stage after conception, increases with gestational age, and declines around term 9 .…”
Section: Introductionmentioning
confidence: 99%
“…It is now widely accepted that 11β‐hydroxysteroid dehydrogenase 2 (11β‐HSD2), a glucocorticoid‐inactivating enzyme, acts as the placental glucocorticoid barrier 4,5 . Several studies have indicated that 11β‐HSD2 catalyzes active glucocorticoids, such as cortisol, into their inactive products, such as cortisone, thus preventing glucocorticoids from passing maternal circulation into the fetus 6‐8 . Ontogeny studies indicate that the expression of 11β‐HSD2 is initiated at a very early stage after conception, increases with gestational age, and declines around term 9 .…”
Section: Introductionmentioning
confidence: 99%
“…11β-HSD-2 is located in the syncytiotrophoblast ( Figure 2) and converts biologically active maternal cortisol into inactive cortisone. This enzyme acts as a 'barrier' to prevent excessive fetal exposure to cortisol derived from the activated maternal system [52,53]. It was previously reported that placental 11β-HSD-2 inactivates the majority of maternal cortisol, however a recent study examining placental glucocorticoid transfer reported that even when 11β-HSD-2 activity was inhibited with carbenoxolone, (a potent HSD inhibitor), less than 10% of maternal cortisol crossed the placenta.…”
Section: Placental Glucocorticoid Receptors and Transportersmentioning
confidence: 99%
“…It was previously reported that placental 11β-HSD-2 inactivates the majority of maternal cortisol, however a recent study examining placental glucocorticoid transfer reported that even when 11β-HSD-2 activity was inhibited with carbenoxolone, (a potent HSD inhibitor), less than 10% of maternal cortisol crossed the placenta. This finding suggests other mechanisms are active in protecting the fetus from high maternal cortisol levels [53]. It has been suggested that due to the significantly higher cortisol concentrations in the maternal circulation compared to the fetal circulation, relatively small changes in 11β-HSD-2 activity may result in clinically significant alterations in fetal glucocorticoid exposure [28].…”
Section: Placental Glucocorticoid Receptors and Transportersmentioning
confidence: 99%
“…This enzyme limits fetal exposure to maternal GC because the predominant activity of placental HSD11B2 is oxidation of maternal cortisol to the inactive GC, cortisone. However, this enzyme only prevents approximately 80–90% of maternal cortisol from crossing the placenta [48, 49]. Expression of HSD11B2 increases throughout pregnancy with a rapid decline late in the third trimester.…”
Section: Antenatal Gc Exposurementioning
confidence: 99%